An updated phylogeography and population dynamics of porcine circovirus 2 genotypes: are they reaching an equilibrium? - Franzo, Giovanni; Tucciarone, Claudia Maria; Legnardi, Matteo; Drigo, Michele; Segalés, Joaquim (Frontiers in Microbiology, 2024)
IntroductionPorcine circovirus 2 (PCV2) emerged more than three decades ago as one of the most impactful pathogens in the swine industry. Despite being a DNA virus, one of the hallmarks of PCV2 is its high evolutionary rate, which has led to the emergence of different genotypes, each exhibiting varying degrees of evolutionary success. Current knowledge suggests the occurrence of three main waves of genotype dominance, alternating over time (i.e., PCV2a, PCV2b, and PCV2d), alongside less prevalent genotypes. However, although PCV2d is currently the most common genotype nowadays, the others continue being circulating in the pig population.MethodsThe present study reconsidered the epidemiological and evolutionary patterns of PCV2 genotypes using phylodynamic analyses, benefiting from an almost 10-fold increase in ORF2 sequence availability compared to previous studies. Additionally, a phylogeographic analysis was performed to investigate viral dispersal patterns and frequency, and the selective pressures acting on the capsid protein were estimated and compared among genotypes.ResultsWhile successive emergence of major genotypes was confirmed, this study extends previous findings by revealing subsequent prevalence fluctuations of PCV2a and PCV2b after their initial decline. This evolutionary process may represent an example of balancing selection, specifically negative frequency-dependent selection, where a genotype fitness diminishes as it becomes more common, and vice versa. Variations in genotype- or clade-specific immunity—affected by the local prevalence of viral groups—combined with the periodic introduction of strains that have independently evolved in different regions, may have led to fluctuations in the population dynamics of major genotypes over time. These fluctuations were associated with ongoing evolution and variations in the capsid amino acid profile.DiscussionThese findings have profound implications for future control strategies. Although PCV2d remains the most prevalent and widespread genotype, other genotypes should not be neglected. Control strategies should thus target the entire PCV2 population, with a focus on fostering broader and more cross-protective immunity.